Arch bridges proceedings of the First International Conference on Arch Bridges held at Bolton, UK on 3-6 September 1995 - Melbourne, C. (Thomas Telford, 1995)
This text brings together current knowledge on all aspects of bridge behaviour, covering developments in construction, design analysis, repair and maintenance. Case histories are used to illustrate the methods used.